New Media and Phenomenon of "Hijrah Keberagamaan" (Internal Conversion) In The Milenial Era - Pardianto Pardianto; Puspita Ayu Shavira (Proceedings of International Conference on Da'wa and Communication, 2020)
This article discusses the role of New Media in encouraging the occurrence of "Religious internal conversion". By using discourse analysis on the social media Twitter, this study revealed that new media characteristics, particularly user-generated content and interactivity characteristics, are not only able to exchange religious messages that encourage people to carry out the religious internal conversion but are also able to construct religious identity in accordance with certain religious values. In this context, the religious identity of the community in new media culture more represents religious symbolism than the substantial.